An In-House Time Tracking Application Development with a Low-To-No-Code Platform - Tanharaphan, Sorn; Rodvanich, Thanabadee; Aupasao, Yatawee; Kaothanthong, Natsuda (Journal of Applied Informatics and Technology, 2025)
We demonstrate a procedure exhaustively to develop an in-house application without requiring database establishment and technician using a low-to-no-code (LCNC) platform that aligns with the organization’s business case for tracking working time and leave request of employees. We developed the application using Google AppSheet and Google Sheets for data storage. The proposed application has three main functions to accurately collect a daily clock-in, clock-out, retrieve the total number of working hours in the current month, and deal with leave requests that align with the organization’s regulations. Furthermore, there are three functions for an administrative employee manage the staff’s information, generate a monthly work report, and perform leave request approvement. The application has been tested at the Artificial Intelligence Association Thailand (AIAT), where time tracking and leave request were previously managed with paper-based. The usability test shows that the staff takes on average less than 1 minute to perform a daily clock-in and clock-out, less than 2 minutes to complete a leave request as well as cancel the submitted request. The learnability test shows that the users take less than 1 minute to complete the daily working timestamp and send leave requests.